Applications of Karry-Kalim-Adnan Transformation (KKAT) to Mechanics and Electrical Circuits. (4th July 2022) - Iqbal, Karry; Kalim, Muhammad; Khan, Adnan
Abstract : In this paper, we have used the new integral transformation known as Karry-Kalim-Adnan transformation (KKAT) to solve the ordinary linear differential equations as well as partial differential equations. We have used KKAT to solve the problems of engineering and sciences specially electrical and mechanical problems. Also, we have established the comparison between KKAT and existing transformations. We have determined the KKAT of error functions and complementary error function. The fundamental purpose of this research paper is to transform the given problem into the easier form to get its solution.